Ноосферні ідеї В.І. Вернадського та сучасні космологічні моделі Всесвіту - Колтачихіна, О.Ю. (Наука та наукознавство, 2012)
The analysis of V.I. Vernadsky’s works devoted to noosphere is contained, their link with contemporary cosmologic models of the Universe is shown.